Increasing Knowledge Through Health Education About Early Detection Of Systemic Lupus Erythematosus (SLE) - Zahrotul Jannah; Anie Trie Indiartinie; Imamatul Faizah; Firnanda Erindia (Sean Institute, 2023)
Lupus is not widely known in the community. The number of people affected by lupus is higher than those affected by AIDS. However, the high number of lupus patients is related to the public's knowledge about lupus. The implementation of this community service activity aims to educate patient families about early prevention of systemic lupus erythematosus (SLE). The method used in this community service activity is providing health education. This activity was conducted in March 2023 and was attended by 20 families of SLE patients in Az-Zahra 1 room at Jemursari Hospital, Surabaya. The research results show that the activity has achieved success according to the predetermined success indicators, which include enthusiastic participation of the attendees and a significant increase in knowledge among the patient families after the education. In conclusion, this community service activity can be conducted in the vicinity of the hospital to increase awareness and knowledge regarding SLE.